Study of apatite layer formation on SBF-treated chitosan composite thin films. (October 2018) - Lewandowska, Katarzyna; Furtos, Gabriel
Abstract: Surface modifications of thin films based on chitosan (Ch), pure Ch and either Ch/montmorillonite (MMT) or Ch/nanoclay composites, were characterised by infrared spectroscopy (ATR-FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Biomineralisation of the Ch-based materials without any prior surface treatment was evaluated by immersing films in simulated body fluid (SBF) at 37 °C for 14 days. Samples were compared before and after soaking. Results obtained from SEM-EDX, AFM, and infrared spectroscopy (ATR-FTIR) were compared, and all prepared films showed growth of a new phase containing calcium. The composition of thin films influenced the amount of new phase formed as well as the degree of crystallinity of the newly formed phase. The largest increase was observed for the Ch composite with modified nanoclay. Moreover, increased growth of the new phase on the surface of films after immersion in SBF solution significantly influenced the thermal properties of the materials. Highlights: This paper focused on the development and characterisation of new thin films based on chitosan composites. SEM-EDX and AFM microscopy and infrared spectroscopy showed growth of a new phases containing calcium in all prepared films. The composition of thin films influenced the amount and crystallinity of new formed phases. The largest increase was observed for chitosan composite with modified nanoclay (contains 25% of octadecylamine). The new phase provides a thermal barrier and decreases mass loss.